Hypervisible: About network cameras and Societies of Control - Lapenda, Agustina (InMediaciones de la Comunicación, 2024)
This article discusses the use of network cameras as surveillance technologies in the context of today’s control societies. The analysis is through the practice of observation and collection of images from surveillance devices that are transmitted online in an unprotected way. If these cameras are not properly secured, they can be viewed and even operated remotely by any person or robot connected to the Internet. Hence, their transmissions can be subject to unintended uses and anonymous interventions of various kinds. The work dialogues with classic and contemporary studies on the subject and investigates the technical functioning of these devices, their relation with surveillance practices and contemporary security discourses, their exposure on the Internet and their political potential derived from the risks promoted by their vulnerability.